Cattle movements and trypanosomes: restocking efforts and the spread of Trypanosoma brucei rhodesiense sleeping sickness in post-conflict Uganda - Selby, Richard (BioMed Central, 2013)
BACKGROUND: The northwards spread of acute T. b. rhodesiense sleeping sickness in Uganda has been linked to cattle movements associated with restocking following the end to military conflict in 2006. This study examined the number of cattle traded from T. b. rhodesiense endemic districts, the prevalence of the parasite in cattle being traded and the level of trypanocidal treatment at livestock markets. METHODS: Between 2008 and 2009 interviews were carried out with government veterinarians from 20 districts in Uganda, 18 restocking organisations and numerous livestock traders and veterinarians. Direct observations, a review of movement permit records (2006 to 2008) and blood sampling of cattle (n = 1758) for detection of parasites were also conducted at 10 livestock markets in T. b. rhodesiense endemic districts. RESULTS: Records available from 8 out of 47 identified markets showed that 39.5% (5,238/13,267) of the inter-district cattle trade between mid-2006 and mid-2008 involved movement from endemic areas to pathogen-free districts. PCR analysis showed a prevalence of 17.5% T. brucei s.l. (n = 307/1758 [95% CI: 15.7-19.2]) and 1.5% T. b. rhodesiense (n = 26/1758 [95% CI: 0.9-2.0]) from these same markets. In a two-year period, between late-2006 to late-2008, an estimated 72,321 to 86,785 cattle (57, 857 by 18 restocking organisations and 10,214 to 24,679 by private traders) were imported into seven pathogen-free northern districts, including districts that were endemic for T. b. gambiense. Between 281 and 1,302 of these cattle were likely to have carried T. b. rhodesiense. While governmental organisations predominantly adhered to trypanocidal treatment, most Non-Governmental Organisations (NGOs) and private traders did not. Inadequate market infrastructure, poor awareness, the need for payment for drug treatments, and the difficulty in enforcing a policy of treatment at point of sale contributed to non-compliance. CONCLUSION: With increasing private trade, preventing the spread of Rhodesian sleeping sickness in Uganda requires government support to ensure mandatory trypanocidal treatment at livestock markets, investment in market infrastructure and possible drug subsidy. Mapping the northern reaches of T. b. rhodesiense in livestock and preparation of risk assessments for cattle trading could mitigate future outbreaks.